Charging Strategy for Electric Vehicles Considering Consumer Psychology and Trip Chain - Gou, Jiwei; Lin, Changsheng; Li, Jun; Geng, Bo; Li, Zhi; Cao, Yang; Li, Yang; Bao, Yuqing (Frontiers in Energy Research, 2021)
As a kind of movable storage device, the electrical vehicles (EVs) are able to support load shaving through orderly charging. The existing researches mostly focus on the design of EVs charging control technology with little consideration of trip-chain-based consumer psychology of EV owners. To fill this gap, this article proposes a price-based orderly charging strategy for EVs considering both consumer psychology and trip chain. Then, the load shaving problem is transformed into a multiobjective optimization problem, to minimize peak-to-valley difference and network loss. A time-of-use price optimization model based on consumer psychology is established to describe the charging behavior of EV owners influenced by electricity price. Finally, the examples verify the feasibility of the proposed strategy by comparing the impact of EVs connected to grid under different ratios, different load transfer rates, and different scenarios.